History of prenatal cardiology in the world and in Poland - Biały, Łucja H.; Respondek-Liberska, Maria (Prenatal Cardiology, 2025)
Prenatal cardiology is a relatively new field of medicine, referring to the circulatory system of the fetus, and it combines different disciplines, such as embryology, physiology, genetics, and cardiology. Its main purpose is the detection and diagnosis of congenital heart defects (CHD) and other disorders of the fetal cardiovascular system. Although seemingly new, it dates back to the 17th century, when the cardiovascular system was first described by anatomists, such as William Harvey and later Johann Friedrich Meckel and Caspar Bartholin. However, nowadays it has developed into fetal cardiac assessment done via ultrasound or fetal MRI. Its rapid development started in the 1970s and 1980s, and it is still a vastly studied subject in fetal cardiology centres all over the world.